Pemanfaatan Media Sosial Sebagai Komunikasi Kreatif Institusi Pendidikan Tinggi Indonesia di Masa Pandemi COVID-19 - Haris Suhendra (Business Economic, Communication, and Social Sciences (BECOSS) Journal, 2021)
The COVID-19 pandemic has forced higher education institutions to change the way they communicate so that the number of new students can continue to grow. The use of social media is a strategy for higher education institutions that must be carried out in building awareness and strong relationships with students and alumni to achieve this growth. Therefore, this study aims to look at the performance of social media during the COVID-19 pandemic by examining upload movement activities on social media. The focus of this research is using social media analytics through performance metrics Impressions, Audience Demographics & Growth, Publishing Behavior, Engagement. The object of this research is to study all activity uploads on Facebook, Instagram and Tiktok during the period July 1, 2020 to June 30, 2021. The frequency of uploads is collected per day and analyzed for one year. This study analyzes the content, frequency and time period of uploads on Facebook, Instagram and Tiktok. The results of this study show the performance of Social Media metrics on Instagram, Facebook and Tiktok by comparing the performance of the research period taken in this study with the previous one year period. Higher Education Institutions are advised to use Social Media as an effective creative communication channel to build the advantages of Higher Education Institutions and build relationships with the public during the COVID-19 pandemic.